2012
DOI: 10.1007/s10549-012-2286-z
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen adherence and its relationship to mortality in 116 men with breast cancer

Abstract: Recent studies have revealed that many, perhaps most women with hormone-responsive breast cancer have low adherence to tamoxifen adjuvant hormonal therapy. However, limited data are available on tamoxifen adherence in male breast cancer (MBC) patients. The goal of this study was to assess tamoxifen adherence and its relationship to mortality in MBC patients. A cohort of 116 men who were diagnosed with receptor-positive breast cancer between June 1987 and July 2012 was recruited for the study using the cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 46 publications
1
34
0
1
Order By: Relevance
“…Although there was an overall increase in the use of adjuvant endocrine therapy during the study period, nearly one‐third of men with ER+ breast cancer did not receive any endocrine therapy. Furthermore, we were unable to assess long‐term compliance or duration of use in the current study, both of which may be an issue in men . Further studies evaluating factors influencing the decision to use or not use adjuvant endocrine therapy, which to our knowledge is the most effective form of systemic therapy for ER+ breast cancer, are needed.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although there was an overall increase in the use of adjuvant endocrine therapy during the study period, nearly one‐third of men with ER+ breast cancer did not receive any endocrine therapy. Furthermore, we were unable to assess long‐term compliance or duration of use in the current study, both of which may be an issue in men . Further studies evaluating factors influencing the decision to use or not use adjuvant endocrine therapy, which to our knowledge is the most effective form of systemic therapy for ER+ breast cancer, are needed.…”
Section: Discussionmentioning
confidence: 90%
“…6B). It is possible that radiotherapy may be more beneficial in this subgroup of men compared with women due to poor compliance with endocrine therapy 35,36 or to the unique tumor biology in men. 37 In terms of the postmastectomy setting, we observed that radiotherapy was associated with poor overall survival in the entire cohort on univariate analysis, which we believed was most likely due to higher risk disease features in those patients because this difference was not noted on multivariate analysis adjusting for disease stage, reflecting the appropriate use of postmastectomy radiotherapy in patients with more advanced tumors.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 However, the median age in those studies was between 57 and 63 years. Although variables related to menopausal symptoms were close to statistical significance in univariate analyses, they did not reach the prespecified threshold to be included in our multivariable analysis.…”
Section: Discussionmentioning
confidence: 97%
“…36; Table 2). In a small study of 116 men with breast cancer, overall survival was greater in those adherent to tamoxifen adjuvant therapy (37).…”
Section: Adjuvant Endocrine Therapy Adherence and Clinical Outcomementioning
confidence: 97%